Rose's rainbow - Walshaw; Sam (Mascot Koala Books, 2010)
The story follows a young girl named Rose who is struggling with her feelings after moving to a new town. One day, she discovers a magical rainbow that appears to be linked to her emotions. With the help of her new friends and a bit of courage, Rose learns to embrace her feelings and find joy in her new surroundings. The book beautifully combines themes of friendship, self-acceptance, and the magic of believing in oneself.